1986
DOI: 10.3354/meps030275
|View full text |Cite
|
Sign up to set email alerts
|

Formation and disruption of aggregations of Mytilus edulis in the fouling community of San Francisco Bay, California

Abstract: Successional dynamics of a fouling assemblage in San Francisco Bay were studied on a series of formica plates. Hydroids and barnacles were found to accelerate rates of succession to mussel dominance by fachtating recruitment of young mussels. Development of hydroid colonies along the borders of plates produced an edge effect that was reflected in the pattern of recruitment of mussels onto plates. The importance of edge-to-center ratios on plates of different sizes and shapes to rates of succession is discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Larval survival and development is dependent upon species-specific temperature and turbidity ranges, and markedly af-fected by fluctuations in food abundance, food quality and predator abundance. These biotic and abiotic parameters affect various larval species differently, and resultant interannual variations in the composition of larval stocks surviving to metamorphosis can markedly influence benthic community composition and structure (Thorson, 1966;Osman, 1977;Okamura, 1986). For example, intense filtration by large stocks of resident bivalve species, or a series of unusually strong recruitments of planktivorous predators, may explain the low larval densities in Schleswig-Holstein in comparison with other areas.…”
Section: Discussionmentioning
confidence: 99%
“…Larval survival and development is dependent upon species-specific temperature and turbidity ranges, and markedly af-fected by fluctuations in food abundance, food quality and predator abundance. These biotic and abiotic parameters affect various larval species differently, and resultant interannual variations in the composition of larval stocks surviving to metamorphosis can markedly influence benthic community composition and structure (Thorson, 1966;Osman, 1977;Okamura, 1986). For example, intense filtration by large stocks of resident bivalve species, or a series of unusually strong recruitments of planktivorous predators, may explain the low larval densities in Schleswig-Holstein in comparison with other areas.…”
Section: Discussionmentioning
confidence: 99%
“…During succession, parts of marine hard substrates often become dominated by mussels (Reusch & Chapman 1997;Stachowitsch et al 2002), which are strong competitors for space (e.g. Okamura 1986;Enderlein & Wahl 2004). In the North Sea the blue mussel Mytilus edulis Linnaeus, 1758 is one of the dominant species in the upper sections of hard substrates (Hardy 1981;Garcia 1991;Leewis et al 1994) including offshore sites (Wolfson et al 1979;Forteath et al 1982;Page & Hubbard 1987;Whomersley & Picken 2003;Buck 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Schoener (1984) and Judge et al (1988) have considered the variability in fouling among replicate coupons. The area and the dimensions of coupons can also have a significant effect on the recruitment of sessile species and ecological succession (Schoener & Schoener, 1981;Okamura, 1986;Karande & Swami, 1988). It is equally important to understand how fouling organisms select their niches over an available area.…”
Section: Introductionmentioning
confidence: 97%
“…Schoener and Schoener (1981), in an examination of species composition and succession on varying coupon sizes, observed that colonisation was more rapid along the edges and that small coupons became more quickly filled-in. Okamura (1986) studied the pattern of recruitment of Mytilus edulis and concluded that the development of hydroids along the borders of test coupons had a significant effect on the succession of the mussel. She also considered the importance of edge-to-centre ratios over coupons of varying sizes on the successional dynamics of M. edulis.…”
Section: Introductionmentioning
confidence: 99%